Praktik Jual Beli Kotoran Hewan Ternak Tanpa Timbangan Perspektif Hukum Ekonomi Syariah (Studi Di Peternakan Wo Dumen, Kecamatan Alam Barajo, Kota Jambi, Provinsi Jambi) - Aldi S Saputra; Fauzi Muhammad; Triska Wulan Dari (CV. ITTC INDONESIA, 2026)
In everyday community life, buying and selling activities are common. At Wo Dumen Farm, one of these activities is the sale of cow manure in addition to the trade of livestock such as cows, buffaloes, and goats. The manure, which is used as fertilizer, is packaged in sacks and collected by buyers at a mutually agreed price. However, in its packaging, no accurate weighing is carried out; instead, the process relies only on estimation before being put into sacks. From the perspective of Islamic Economic Law, such a practice contains elements of gharar (uncertainty), since the weight or quantity of the goods being transacted must be clear and precise. This study aims to examine the sale of livestock manure from the perspective of Islamic Economic Law at Wo Dumen Farm, Alam Barajo District, Jambi City, Jambi Province.This research uses an empirical legal method with a case study approach. Primary data were obtained through observation, interviews, and documentation conducted at Wo Dumen Farm, Alam Barajo District, Jambi City, Jambi Province. Secondary data were collected from literature such as journals, books, research reports, and other related materials. Tertiary data were obtained from the Indonesian Dictionary (KBBI), legal dictionaries, and various other references. Data processing and analysis were conducted using a qualitative descriptive approach through several stages: data collection, data reduction, data analysis, data presentation, conclusion, and research report. The findings show that the sale of livestock manure at Wo Dumen Farm is carried out using the sack system without any fixed weighing or measurement. This transaction pattern falls into the category of jizāf sale (sale without measurement), which is permissible in Islamic Economic Law as long as the pillars and conditions of sale are fulfilled, namely the presence of a seller, a buyer, the object of the contract, and the declaration of offer and acceptance (ijab and qabul).In this context, Sharia principles such as the principle of permissibility, justice, public benefit (maslahah), and enjoining good while forbidding wrong (amar ma’ruf nahi munkar) can be properly applied. Therefore, the sale of livestock manure without weighing at Wo Dumen Farm is considered valid according to Islamic Economic Law. Moreover, this practice is not only legitimate from a Sharia perspective but also holds legitimacy in economic and environmental terms.